FUNGSI MITE ASAL MULA PADI DALAM TRADISI AGRARIS MASYARAKAT DAYAK BIDAYUH DI KALIMANTAN BARAT - Bambang H. Suta Purwana (Jantra., 2019)
This study aims to reveal the relationship between the myth of the origin of rice that belongs to the Dayak Bidayuh people and their agrarian culture. This qualitative descriptive research obtained the primary and secondary data from library research. The function of the myth of the origin of rice is to explain when the Dayak Bidayuh people started rice cultivation. The myth has also become the key reference for preparing offerings in particular ritual ceremonies. That men are not circumsized is also exemplified in this myth. For the Dayak Bidauh people, the myth of the origin of rice also serves as the legitimate source of what should be in existence or happen in their social life.